2016
DOI: 10.1136/bmjopen-2015-009535
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the risk of heart disease following acute ischaemic stroke: a meta-analysis of over 50 000 participants

Abstract: ObjectiveFollowing an acute stroke, there is a high risk of recurrence. However, the leading cause of mortality following a stroke is due to coronary artery disease (CAD) and myocardial infarction (MI) but that risk has not been robustly quantified. We sought to reliably quantify the risk of ischaemic heart disease (IHD) in patients presenting with acute ischaemic stroke (AIS) in the absence of a known cardiac history.SettingA meta-analysis study. PubMed, MEDLINE, EMBASE and Google Scholar were searched for po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
50
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 50 publications
2
50
0
3
Order By: Relevance
“…Although Gunnoo et al. reported that a third of patients with ischemic stroke demonstrated asymptomatic coronary artery diseases, the relationship between IHD and post‐stroke seizures remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Gunnoo et al. reported that a third of patients with ischemic stroke demonstrated asymptomatic coronary artery diseases, the relationship between IHD and post‐stroke seizures remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, our multivariate analysis also showed that underlying IHD is an independent risk factor for post-stroke seizures. Although Gunnoo et al reported that a third of patients with ischemic stroke demonstrated asymptomatic coronary artery diseases, 23 the relationship between IHD and post-stroke seizures remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…3 Nevertheless, real-world data suggest that the incidence of MI after AIS may not be as high as theoretically expected. 5 The most recent systematic review calculated that the yearly risk of post-stroke MI is 1.67%. 4 Another meta-analysis showed similar results: ischaemic stroke was shown to be associated with an overall risk of MI in the year following stroke of 3% (1.0-5.0).…”
Section: Introductionmentioning
confidence: 99%
“…4 Another meta-analysis showed similar results: ischaemic stroke was shown to be associated with an overall risk of MI in the year following stroke of 3% (1.0-5.0). 5 The most recent systematic review calculated that the yearly risk of post-stroke MI is 1.67%. 6 Given that there is significant overlap between stroke secondary preventative therapies and acute coronary syndrome (ACS) primary prevention, it may not seem surprising that the annual incidence of post-stroke MI is not as high expected in such a highly co-morbid population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation